1987
DOI: 10.1111/j.1600-0528.1987.tb00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐year follow‐up of caries prevalence and incidence in children and young adults in Espoo, Finland Oral Epidemiology

Abstract: This follow-up of the oral health of children and young adults in Espoo, Finland, has been carried out using annual check-ups done by dentists at the Espoo Health Center. There was about 80% participation in municipal dental care by 3- to 18-yr-olds. Each age group included 1700-2300 individuals. The DMFT-index for 12-yr-olds was 6.9 initially and only 2.2 at the end of the 12-yr follow-up. The reduced DMFT and increased number of clinically caries free children is probably the cumulative effect of various pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…DMFT scores in 12-year-old children have also been reported for Finland (2.2) (Luoma and Ronnberg, 1987) and for Italy (3.03) (Giannico, 1987). In Hamburg, in the same age group, a DMFT score of 6.33 was found by Franz and G6tze (1983).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…DMFT scores in 12-year-old children have also been reported for Finland (2.2) (Luoma and Ronnberg, 1987) and for Italy (3.03) (Giannico, 1987). In Hamburg, in the same age group, a DMFT score of 6.33 was found by Franz and G6tze (1983).…”
Section: Discussionmentioning
confidence: 73%
“…According to Schwarz (1987), 54% and 16%, respectively, of Danish children were caries-free at the ages of 5 and 12. Reporting the results of a 12-year prevention follow-up of Finnish children, Luoma and Ronnberg (1987) observed that, initially, only 10% of the 6-year-old children were caries-free; this percentage was 57% 12 years later.…”
Section: Discussionmentioning
confidence: 98%
“…Official statistics and research reports have shown an appreciable decline in the occurrence of past and present caries in recent years in Finland [Rytomaa et al, 1980;Milen et al, 1986;Nordblad, 1986], A report from the health centre of the city of Espoo in southern Finland stated that teenagers in 1984 had about 6 DMF teeth and 1 decayed tooth (DT) less than similar teenagers 10 years earlier [Luoma and Ronnberg, 1987], Similar trends in caries prevalence in children and adolescents have been reported for many industrial ized countries [Graves and Stamm, 1985;Bille et al, '986;Birkeland and Bragelien, 1987;Hargreaves et al, 1987;Hailing and Birkhed, 1988;Carr, 1988]. Most reports have dealt only with the mean value of DMFT and its components.…”
mentioning
confidence: 99%
“…The 14-year reductions are consistent with a prop- agation of the 7-year cumulative effects observed, with the observed 55% reduction slightly larger than the 45 or 49% expected values one would obtain from the CGM or DSR model. A report of 12-year follow-up for Finnish subjects by Luoma and Ronnberg [14] was published in 1987. Their findings are summarized in table 7.…”
Section: Repeated Cross-sectional Studiesmentioning
confidence: 99%